Potential threats of glacial lake changes to the Sichuan-Tibet Railway - Menger Peng; Guoqing Zhang; Jinyuan Yu; Weicai Wang; Fenglin Xu; Sonam Rinzin (Journal of Glaciology)
The Sichuan-Tibet Railway, China's second inland railway to Tibet, is currently being constructed and will run between Chengdu and Lhasa. It will cross the southeastern Tibetan Plateau and be surrounded by glacial lakes, some of which may pose a threat of glacial lake outburst flood (GLOF) events. Both the specific location and the outburst susceptibility of these glacial lakes are largely unknown. In this study, we mapped the glacial lakes using declassified Corona KH-4 and Hexagon KH-9 from the 1960s and Sentinel-2 imagery from 2020 and assessed their spatio-temporal changes. GLOF-susceptibility criteria were established based on historical GLOF events. The results show that the total area (number) of glacial lakes has increased by 22% (20%) from 126.1 ± 2.4 km2 (1662 lakes) in the 1960s to 153.6 ± 11.1 km2 (1994 lakes) in 2020. Of these lakes, this study identified 38 very high and 85 high GLOF-susceptibility lakes; mainly distributed along the Bomi-Nyingchi railway section in the Parlung Zangbo River basin. Four of the very high GLOF-susceptibility glacial lakes may pose a threat to the railway and will require monitoring. The insights from this study can be used to mitigate the risk of GLOFs during the construction and maintenance of the Sichuan-Tibet Railway.